Mineralocorticoid Receptor Pathway Is a Key Mediator of Carfilzomib-induced Nephrotoxicity: Preventive Role of Eplerenone. Issue 11 (18th November 2022) - Efentakis, Panagiotis; Lamprou, Sofia; Makridakis, Manousos; Barla, Ioanna; Nikolaou, Panagiota-Efstathia; Christodoulou, Andriana; Dimitriou, Costantinos; Kostomitsopoulos, Nikolaos; Ntanasis-Stathopoulos, Ioannis; Theochari, Irene; Gavriatopoulou, Maria; Gakiopoulou, Harikleia; et al.
Abstract : Carfilzomib is an irreversible proteasome inhibitor indicated for relapsed/refractory multiple myeloma. Carfilzomib toxicity includes renal adverse effects (RAEs) of obscure pathobiology. Therefore, we investigated the mechanisms of nephrotoxicity developed by Carfilzomib. In a first experimental series, we used our previously established in vivo mouse models of Carfilzomib cardiotoxicity, that incorporated 2 and 4 doses of Carfilzomib, to identify whether Carfilzomib affects renal pathways. Hematology and biochemical analyses were performed, while kidneys underwent histological and molecular analyses. In a second and third experimental series, the 4 doses protocol was repeated for 24 hours urine collection and proteomic/metabolomic analyses. To test an experimental intervention, primary murine collecting duct tubular epithelial cells were treated with Carfilzomib and/or Eplerenone and Metformin. Finally, Eplerenone was orally co-administered with Carfilzomib daily (165 mg/kg) in the 4 doses protocol. We additionally used material from 7 patients to validate our findings and patients underwent biochemical analysis and assessment of renal mineralocorticoid receptor (MR) axis activation. In vivo screening showed that Carfilzomib-induced renal histological deficits and increased serum creatinine, urea, NGAL levels, and proteinuria only in the 4 doses protocol. Carfilzomib decreased diuresis, altered renal metabolism, and activated MR axis. This was consistent with the cytotoxicity found in primary murine collecting duct tubular epithelial cells, whereas Carfilzomib + Eplerenone co-administration abrogated Carfilzomib-related nephrotoxic effects in vitro and in vivo. Renal SGK-1, a marker of MR activation, increased in patients with Carfilzomib-related RAEs. Conclusively, Carfilzomib-induced renal MR/SGK-1 activation orchestrates RAEs and water retention both in vivo and in the clinical setting. MR blockade emerges as a potential therapeutic approach against Carfilzomib-related nephrotoxicity.